Optimization of Specifications for Scaled-Up Fixed Rabies Virus Cultivation (“Moscow 3253” Strain) in Vero Cell Culture - S. V. Generalov; E. G. Abramova; Zh. V. Matveeva; I. M. Zhulidov; L. V. Savitskaya; O. A. Lobovikova (Проблемы особо опасных инфекций, 2014)
/cell, using maintenance media 199 with admixture of 0.1 % human serum albumin or 2 % bovine serum. Optimum media volume in the roll-bottle for fixed rabies virus strain, “Moscow 3253”, cultivation is 200-400 ml. It depends upon the proliferating surface area. Specifications stated above provide for the obtainment of culture liquid with rabies virus titer - 1:256 - 1:512, if assayed in ELISA. This cultural virus is recommended as a basis for immunization material obtainment with a view to produce anti-rabies immunoglobulin from equine blood serum.